Reasons for Guardian-Relinquishment of Dogs to Shelters: Animal and Regional Predictors in British Columbia, Canada - Eagan, Bailey H.; Gordon, Emilia; Protopopova, Alexandra (Frontiers in Veterinary Science, 2022)
Dogs are relinquished to animal shelters for animal-related or guardian-related reasons. Understanding what drives relinquishment patterns is essential for informing intervention opportunities to keep animals with their guardians. Whereas, overall reasons for relinquishment in a given shelter system have been well explored, analysis of human and animal predictors of relinquishing for a specific reason has not been previously attempted. We used characteristics of relinquishment including year, population of the relinquishing guardian's region, health status of the dog, breed, age group, weight, and sex to predict reasons for dog relinquishment to British Columbia (BC) Society for the Prevention of Cruelty to Animals (SPCA) shelters across BC between 2008 and 2019 (n = 32,081). Relinquishment trends for puppies and adult dogs were also viewed and described. From 2008–2019, the proportion of dogs relinquished relative to total intake remained consistent (range: 31–35%). Primary reasons reported by guardians were having too many dogs (19%), housing issues (17%), personal issues (15%), financial issues (10%), dog behavior (10%), and guardian health (8%). Over years, an increasing proportion of dogs were relinquished for the reason “too many” (OR = 1.16, 95% CI, 1.10–1.23, p < 0.001) and “behavior” (OR = 1.34, 95% CI, 1.26–1.43, p < 0.001), while a decreasing proportion were relinquished due to financial problems (OR = 0.94, 95% CI, 0.88–1.00, p = 0.047). Being a puppy, mixed breed, small, and from a small or medium population center predicted the reason “too many.” Being a senior, Healthy, or from a medium or large population center predicted the reason “housing issues.” Being a non-puppy, Healthy dog in a large population center predicted the reason “personal issues.” Being a puppy, non-Healthy, female, and from a large population center predicted the reason “financial issues.” Being a larger young adult or adult and Healthy predicted the reason “dog behavior.” Being an adult or senior small dog from a small population center predicted the reason “guardian health.” Particularly promising region-specific intervention opportunities include efforts to prevent too many animals in small population centers, improvement of pet-inclusive housing in large population centers, and providing animal care support in large population centers. Accessible veterinary services, including low-cost or subsidized care, likely benefit dog retention across BC.